NOVEL CHRONOTHERAPEUTIC MULTIPARTICULATE DRUG DELIVERY SYSTEM OF FELODIPINE: AN EFFECTIVE TREATMENT FOR CARDIAC ARRHYTHMIA - Banerjee, Sabyasachi; Shankar, K Ravi; Rajendra, Y Prasad (Indonesian Journal of Pharmacy, 2017)
Arrhythmia follows chronobiology, thus necessitating development of time-dependent formulation for its treatment. The aim of the current work was to develop a solubility-enhanced chronotherapeutic system of felodipine, a widely prescribed anti-arrhythmic. Systematically optimized hot-melt extrusion process was employed to formulate solubility-enhanced extrudates. Film-casting method was adopted for the selection of polymers. Drug released at 5, 15, 30min was taken as response variables in 32 face-centered cube design. Nearly 10-fold increase was observed in the solubility of the optimized extrudates in comparison to pure drug. Physical characterization of the extrudates depicted complete amorphization of drug. Sequential coating was performed on to the extrudates to enable a time-dependent release. In-vitro studies clearly demonstrated that 25% of drug was available rapidly within 10 min of administration. The remaining 75% of drug was available over a period of 4, 8 and 12h. Stability studies performed for 6 months at accelerated conditions depicted no significant change in the physicochemical characteristics of the optimized formulation. In-vivo pharmacokinetic studies conducted in beagle dogs ratified the results of in-vitro studies where a sequential time dependent absorption of felodipine was observed over a period of 12h. Concisely, the studies demonstrated successful development of solubility-enhanced chronotherapeutic system of felodipine.